Foliar Application or Seed Priming of Cholic Acid-Glycine Conjugates can Mitigate/Prevent the Rice Bacterial Leaf Blight Disease via Activating Plant Defense Genes - Pal, Garima; Mehta, Devashish; Singh, Saurabh; Magal, Kalai; Gupta, Siddhi; Jha, Gopaljee; Bajaj, Avinash; Ramu, Vemanna S. (Frontiers in Plant Science, 2021)
Xanthomonas Oryzae pv. oryzae (Xoo) causes bacterial blight and Rhizoctonia solani (R. solani) causes sheath blight in rice accounting for >75% of crop losses. Therefore, there is an urgent need to develop strategies for mitigation of these pathogen infections. Herein, we report the antimicrobial efficacy of Cholic Acid-Glycine Conjugates (CAGCs) against Xoo and R. solani. We show that cholic acid-glycine conjugate C6 is a broad-spectrum antimicrobial, and is also able to degrade the biofilms. Application of C6 did not hamper the plant growth, and showed minimal effect on plant cell membranes. Pre-infection or post-infection exogenous application of C6 on rice susceptible genotype TN1 can mitigate the bacterial load, and improve resistance through upregulation of plant defence genes. We further demonstrate that C6 can induce plant defence responses when seeds were primed with C6 CAGC. Therefore, this study demonstrates the potential of CAGCs as effective antimicrobials for crop protection that can be further explored for field applications.